2013
DOI: 10.3389/fnhum.2013.00007
|View full text |Cite
|
Sign up to set email alerts
|

Early visual experience and the recognition of basic facial expressions: involvement of the middle temporal and inferior frontal gyri during haptic identification by the early blind

Abstract: Face perception is critical for social communication. Given its fundamental importance in the course of evolution, the innate neural mechanisms can anticipate the computations necessary for representing faces. However, the effect of visual deprivation on the formation of neural mechanisms that underlie face perception is largely unknown. We previously showed that sighted individuals can recognize basic facial expressions by haptics surprisingly well. Moreover, the inferior frontal gyrus (IFG) and posterior sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
147
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(164 citation statements)
references
References 81 publications
7
147
2
2
Order By: Relevance
“…In light of previous evidence, we expected that blind individuals would recognize emotions as accurately as sighted individuals, if not better (see Iversen et al, 2015; Kitada et al, 2013; Klinge et al, 2010). In this scenario, preservation of hemispheric lateralization would presuppose that emotion cues garnered from other sensory modalities (e.g., auditory, haptic, and olfactory domains) may be sufficient for the specialization of related emotion processing brain networks.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In light of previous evidence, we expected that blind individuals would recognize emotions as accurately as sighted individuals, if not better (see Iversen et al, 2015; Kitada et al, 2013; Klinge et al, 2010). In this scenario, preservation of hemispheric lateralization would presuppose that emotion cues garnered from other sensory modalities (e.g., auditory, haptic, and olfactory domains) may be sufficient for the specialization of related emotion processing brain networks.…”
mentioning
confidence: 93%
“…Moreover, blind participants outperformed sighted control participants in recognizing negative emotions from body odours (Iversen, Ptito, Møller, & Kupers, 2015) and from prosody (Klinge, Röder, & Büchel, 2010). At the neurophysiological level, it has been reported that blind individuals show enhanced occipital cortex (specifically, the middle and superior occipital gyri) activity during the haptic recognition of facial expressions (Kitada et al, 2013), and enhanced amygdala responses to emotional auditory stimuli (Klinge et al, 2010) as compared with sighted controls. These results are in line with a contemporary view suggesting that early visual deprivation is associated with compensatory behaviors that are intimately related to underlying changes in the overall structural and functional organization of the brain (e.g., Hasson, Andric, Atilgan, & Collignon, 2016; Voss & Zatorre, 2015; for reviews, see Cattaneo et al, 2008; Ricciardi, Bonino, Pellegrini, & Pietrini, 2014).…”
mentioning
confidence: 99%
“…Previous work has shown that the cortical locations of some categorical representations partially overlap in the brains of blind and sighted persons; here we quantify the relative strength of these representations in the two subject groups and the degree of spatial overlap in multiple categories. Second, the majority of studies have investigated the activation of visual regions by linguistic sounds: mostly auditory words, and in one case braille and learned letter soundscapes [with the notable exception of haptic stimulation (18)(19)(20)]. To understand the problem inherent in this limitation, consider trying to study the fusiform face area by presenting written names of people rather than their faces.…”
mentioning
confidence: 99%
“…Prilikom upoznavanja, čak 60% kompletnog utiska o osobi formira se na osnovu neverbalne komunikacije (Mirković, 2008, prema Ilievska, 2010. Izrazi lica igraju ključnu ulogu u razumevanju mentalnog stanja sagovornika (Kunz, Faltermeier & Lautenbacher, 2012 (Kitada et al, 2013). Kulturne razlike i neki situacioni faktori mogu da utiču i na učestalost ekspresije pojedinih emocija (Ghosh, 2010).…”
Section: Uvodunclassified
“…Studije koje su se bavile voljnim izražavanjem emocija pokazuju da se slepe osobe suočavaju sa nizom teškoća u iskazivanju voljnih emocionalnih izraza (Webb, 1977; Rinn, 1991; Galati, Scherer & Ricci-Bitti, 1997). S druge strane, slepi ispitanici mogu da prepoznaju osnovne izraze lica putem dodira, bez obzira na nedostatak ranog vizuelnog iskustva (Kitada, et al, 2013). Preciznost i tač-nost taktilnog prepoznavanja facijalne ekspresije je različita za pojedine emocije.…”
Section: Emocionalna Razmena Kod Osoba Sa Oštećenjem Vidaunclassified